What Influences Shifts in Urban Nature Site Visitation During COVID-19? A Case Study in Tel Aviv-Yafo, Israel - Talal, Michelle L.; Gruntman, Michal (Frontiers in Environmental Science, 2022)
Urban nature sites are crucial places for the promotion of human health and well-being during the COVID-19 pandemic, but there are few interdisciplinary studies that simultaneously investigate the impact of a range of social and environmental factors on potential shifts in urban nature site visitation. We sought to do this by analyzing both geospatial data of the amenities and environmental features of urban nature sites with a web-based survey of urban nature site visitation in Tel Aviv-Yafo, Israel. We found that 53% of surveyed participants decreased visitation during the pandemic, while 26% increased visitation, 21% had no change, and only 1.7% were first-time visitors of urban nature sites. We developed a multiple linear regression model for shifts in visitation frequency during the pandemic, and found that a relative increase in visitation was positively associated with higher ratings of the physical and mental health contribution of the urban nature sites, higher nature maintenance and accessibility ratings, and visiting with a spouse, but negatively associated with variables such as car transportation, visit length, shrub habitat, age, and visiting alone or for romantic dates. Our results suggest that the perceived health benefits and accessibility of urban nature sites could be key in motivating visitation during the pandemic more than the specific environmental features or amenities of these sites. Given the on-going threats of the pandemic and other environmental crises, it is imperative to continue supporting the creation, maintenance, and monitoring of urban nature sites for not only urban ecosystems and biodiversity, but also so that they can contribute to the health of all urban residents.